Culturally integrated interactive worksheets based on maritime Malay context to enhance mathematical literacy in grade VII differentiated learning - Arifin, Yesica Salshabila; Febrian, Febrian; Astuti, Puji (Jurnal Gantang, 2025)
The low level of students’ mathematical literacy, particularly in linking mathematical concepts to daily life, remains a challenge in education. This study develops an interactive Student Worksheet that incorporates Malay maritime culture to enhance seventh-grade students’ mathematical literacy through differentiated learning. Cultural elements such as the traditional game porok and the fish trap bubu are included, since both represent proportional concepts relevant in mathematics. Differentiation is based on diagnostic tests of students’ literacy levels and applied to process and content aspects, adjusted to their readiness. The research follows the ADDIE development model through analysis, design, development, implementation, and evaluation phases. Practicality testing involved one mathematics teacher and 30 students from Class VII.E at SMP Negeri 17 Bintan, while effectiveness testing used the same participants. Data were collected using interviews, validation and practicality questionnaires, and literacy tests adapted from the 2022 PISA framework, focusing on reasoning and problem-solving. The findings show the worksheets is highly valid (88.14%) and practical, with positive responses from the teacher (93%) and students (88.40%). An N-Gain score of 0.75 (high category) confirms effectiveness. These results indicate that the developed worksheets successfully improve students’ mathematical literacy through differentiated learning and the integration of Malay maritime culture.